The knottin-like Blufensin family regulates genes involved in nuclear import and the secretory pathway in barley-powdery mildew interactions - Xu, Weihui; Meng, Yan; Surana, Priyanka; Fuerst, Greg; Nettleton, Dan; Wise, Roger P. (Frontiers in Plant Science, 2015)
Plants have evolved complex regulatory mechanisms to control a multi-layered defense response to microbial attack. Both temporal and spatial gene expression are tightly regulated in response to pathogen ingress, modulating both positive and negative control of defense. BLUFENSINs, small knottin-like peptides in barley, wheat, and rice, are highly induced by attack from fungal pathogens, in particular, the obligate biotrophic fungus, Blumeria graminis f. sp. hordei (Bgh), causal agent of barley powdery mildew. Previous research indicated that Blufensin1 (Bln1) functions as a negative regulator of basal defense mechanisms. In the current report, we show that BLN1 and BLN2 can both be secreted to the apoplast and Barley stripe mosaic virus (BSMV)-mediated overexpression of Bln2 increases susceptibility of barley to Bgh. Bimolecular fluorescence complementation (BiFC) assays signify that BLN1 and BLN2 can interact with each other, and with calmodulin. We then used BSMV-induced gene silencing to knock down Bln1, followed by Barley1 GeneChip transcriptome analysis, to identify additional host genes influenced by Bln1. Analysis of differential expression revealed a gene set enriched for those encoding proteins annotated to nuclear import and the secretory pathway, particularly Importin α1-b and Sec61 γ subunits. Further functional analysis of these two affected genes showed that when silenced, they also reduced susceptibility to Bgh. Taken together, we postulate that Bln1 is co-opted by Bgh to facilitate transport of disease-related host proteins or effectors, influencing the establishment of Bgh compatibility on its barley host.